Pelatihan Pembuatan Pupuk Organik Cair Di Desa Wonggahu Kecamatan Paguyaman Kabupaten Boalemo - Bahri, Syamsul; Mukhtar, Muhammad; Purnomo, Sutrisno Hadi; Hippy, Mohammad Zubair; Ervandi, Mohamad (Universitas Mataram, 2024)
Increasing the production of sweet corn plants to meet the food needs of the community faces quite big challenges, especially in terms of providing environmentally friendly fertilizer. This activity aims to provide training in making liquid organic fertilizer from cow urine for sweet corn fertilizer needs. The location for the activity is in Wonggahu Village, Paguyaman District, which has the potential for cultivating sweet corn because it has the carrying capacity of land and cattle farm waste as raw material for organic fertilizer. The method for making organic fertilizer uses the fermentation method using cattle urine as the raw material. Making liquid organic fertilizer is done by mixing all the ingredients evenly and putting them in a container. Ripening takes place in 7 days. Based on the results obtained, it can be concluded that making liquid organic fertilizer in Wonggahu village can be an alternative fertilizer provider for farmers.